Hemostatic and antithrombotic stewardship programs: A toolkit for program implementation. Issue 6 (15th February 2022) - Dane, Kathryn E.; Naik, Rakhi P.; Streiff, Michael B.; Yui, Jennifer; Shanbhag, Satish; Nesbit, Todd W.; Lindsley, John
Abstract: Hemostatic and antithrombotic agents are high‐risk medications associated with high cost. The importance of anticoagulation stewardship has been recently highlighted by national organizations, but hemostatic stewardship programs remain underutilized. Several established hemostatic and/or antithrombotic stewardship programs have demonstrated a significant impact on the quality and cost of care provided to patients receiving these therapies. This review provides a comprehensive toolkit for development and implementation of combined hemostatic and antithrombotic stewardship programs.